Herbivory is related to taxonomic isolation, but not to invasiveness of tropical alien plants - Dawson, Wayne; Burslem, David F. R. P.; Hulme, Philip E. (Diversity & distributions, 2009)
The enemy release hypothesis is often invoked to explain why some alien plant species become invasive. Here, we investigated relationships between invasiveness, taxonomic isolation and leaf herbivory for tropical alien plant species introduced to a botanical garden in East Africa. Amani Botanical Garden, East Usambara mountains, northeast Tanzania. We measured the proportion of leaves damaged, and the percentage leaf area damaged on individuals of 28 alien plant species. We extracted data on the presence/absence of native congeners and the number of native confamilial species from an inventory of the East Usambara flora. We also obtained data on planting effort for 26 species, from historical records. Linear and generalized linear models were used to analyse the relationships between invasiveness, herbivory and taxonomic isolation. Mean proportion of leaves damaged per species was significantly explained by taxonomic isolation; proportion of leaves damaged increased with the number of native confamilial species and was greater, on average, for species with native congeners than those without native congeners. The mean percentage of leaf area damaged per species could not be explained by any variables considered in this study. There was no relationship between the degree of herbivory or taxonomic isolation and alien plant species invasiveness, but more-invasive species did have a significantly greater planting effort than less-invasive species. The role herbivores play in controlling alien plant invasions has been investigated relatively little in the tropics. In this study, although the amount of herbivory suffered by alien plants was related to taxonomic isolation, we found no evidence for leaf-feeding invertebrates having a significant role in invasion, suggesting that other factors may be responsible for differences in species success.